'Habitus in Extremis': From Embodied Culture to Bio-Cultural Development. (June 2014) - Downey, Greg
Loïc Wacquant argues for a radicalization of the habitus concept provided by Pierre Bourdieu, suggesting that habitus is a site and mode for conducting research, not simply an explanatory or theoretical mechanism. Taking seriously this call to examine skills and communities of practice through apprenticeship, however, requires that the theoretical account of habitus be subject to empirical testing. Moreover, enquiry into communities of practice, especially the subtle psychological, behavioural and even neurological consequences of skill acquisition, means that claims about the habitus can be scrutinized by fields such as psychology, neurology and even human biology. Habitus as a truly open path of inquiry will demand, not wholly novel concepts, but a recognition of when claims about practice are simultaneously testable, and falsifiable, by other forms of empirical enquiry, including the human sciences.